A morphological analysis of Centaurea nigra and its associated taxa in Hertfordshire. (2nd September 2017) - Harris, M.
Abstract : Centaurea nigra is a common grassland species within the variable, taxonomically difficult C. jacea group. C. debeauxii has recently been raised from subspecies to species level prompting an increase in recording. Difficulty in identifying these species is compounded by intra-species variation and the presence of introgressed hybrid swarms comprising not only C. nigra and C. debeauxii as parents but also C. jacea, an introduced species. This study uses multi-variate analytical techniques to identify and test the most diagnostic characters for these taxa. Fifteen morphological characters were measured on a range of herbarium specimens of C. nigra s.l. and principal component analysis was used to identify which characters are the most discriminating. Five selected characters were used in a discriminant analysis to compare Centaurea populations in Hertfordshire occupying a range of habitat types. The outcomes were tested using ANOSIM to test whether there is a significant difference between populations. Capitulum characters are shown to be discriminatory and used to confirm the presence of C. debeauxii and hybrids of C. debeauxii and C. nigra in the county together with evidence of contamination from C. jacea . Populations containing C. debeauxii range from mostly pure downland ecotypes to highly variable hybrid populations dominated by C. debeauxii but which show evidence of C. nigra characteristics. Some hybrid populations are closer to C. nigra and these are interpreted as C. nigra being the local taxon. Different habitat preferences determined by soil, wetness and acidity are confirmed. A method of defining populations is proposed.